Efficiency Increase of Wet Gas Cleaning from Dispersed Admixtures by the Application of Ultrasonic Fields - KHMELEV, Vladimir Nikolaevich; SHALUNOV, Andrey Viktorovich; GOLYKH, Roman Nikolaevich; DOROVSKIKH, Roman Sergeevich; NESTEROV, Viktor Alexandrovich; KHMELEV, Sergei Sergeevich; SHALUNOVA, Ksenija Viktorovna (Archives of Acoustics, 2016)
The article presents the results of research aimed at increase of the efficiency of gas cleaning equipment based on the Venturi tube using high-intensity ultrasound. The model based on known laws of hydrodynamics of multiphase mediums of dust-extraction in Venturi scrubbers was proposed. Modification of this model taking into account ultrasonic field allows evaluating optimum modes (sound pressure level) and conditions (direction of ultrasonic field, square and number of ultrasonic sources) of ultrasonic influence. It is evaluated that optimum for efficient gas cleaning is the mode of ultrasonic action at the frequency of 22 kHz with sound pressure level of 145...155 dB at the installation of two radiators with area of 0.14 m2, four radiators with area of 0.11 m2 or six radiators with area of 0.08 m2 at the angle of 45 degrees to the axis of Venturi tube. Numerical calculations showed that realization of ultrasonic action is the most efficient for the reduction (up to 15 times) of the content of fine-dispersed fraction (2 µm and less), which is impossible to extract without ultrasonic action. The received theoretical results were confirmed by industrial testing by typical dust-extraction plant and used as foundations of development of apparatuses with the radiators of various sizes.